2013
DOI: 10.1002/tect.20075
|View full text |Cite
|
Sign up to set email alerts
|

Thermal‐mechanical modeling of salt‐based mountain belts with pre‐existing basement faults: Application to the Zagros fold and thrust belt, southwest Iran

Abstract: [1] Two-dimensional thermal-mechanical models of thick-skinned, salt-based fold and thrust belts, such as the Zagros, SW Iran, are used to address: (1) the degree of deformation and decoupling between cover and basement rocks due to the presence of a weak salt detachment, (2) the reactivation potential of pre-existing basement normal faults due to brittle or ductile behavior of the lower crust (as related to cold or hot geothermal gradients), and (3) variations in deformation style and strain distribution. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 104 publications
1
20
0
Order By: Relevance
“…Such complex evolution of orogenic systems and associated FTB has also been demonstrated by numerical (e.g. García-Castellanos, Fernàndez & Torné, 1997; Andeweg & Cloetingh, 1998; Beaumont et al 2000; Jammes & Huismans, 2012; Ruh, Kaus & Burg, 2012; Nilfouroushan et al 2013; Erdős et al 2014) and analogue modelling studies (e.g. Mugnier et al 1997; Nilfouroushan & Koyi, 2007; Malavieille, 2010; Graveleau, Malavieille & Dominguez, 2012; Perrin et al 2013).…”
Section: Introductionmentioning
confidence: 63%
“…Such complex evolution of orogenic systems and associated FTB has also been demonstrated by numerical (e.g. García-Castellanos, Fernàndez & Torné, 1997; Andeweg & Cloetingh, 1998; Beaumont et al 2000; Jammes & Huismans, 2012; Ruh, Kaus & Burg, 2012; Nilfouroushan et al 2013; Erdős et al 2014) and analogue modelling studies (e.g. Mugnier et al 1997; Nilfouroushan & Koyi, 2007; Malavieille, 2010; Graveleau, Malavieille & Dominguez, 2012; Perrin et al 2013).…”
Section: Introductionmentioning
confidence: 63%
“…Numerical modelling studies have recently addressed the structural style of mountain belts and have shown that the rheology of the basement–cover sequence and the rheological layering of the lithosphere have a strong control on this style (Jammes & Huismans, 2012; Nilfouroushan et al 2013; Bauville & Schmalholz, 2015). Jammes & Huismans (2012) showed by means of a 2D thermomechanical modelling approach that the relative strength of the frictional-plastic and viscous rheologies in the lithosphere affects the way it deforms in orogenic settings.…”
Section: Rheological Aspects Of Basement-involved Shortening and Impomentioning
confidence: 99%
“…For example, subsurface data, earthquake locations and mechanisms and fracture analysis can be used to infer the characteristics of these basement faults (Berberian 1995;Hessami et al 2001a;Bahroudi and Talbot 2003;Sepehr and Cosgrove 2005;Mobasher and Babaie 2008;Farzipour-Saein et al 2009a, 2013Nilfouroushan et al 2013). Our fracture analysis, based on remote sensing and filed observations, shows that excluding the fold-related fractures, the rest of the fractures (i.e., trans-fold fractures) can be categorized in four Mean direction of each set is marked by red line, and two statistical parameters, e.g., circular mean value and circular standard deviation, are presented for each zone sets based on their directions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1), including the Foredeep, the Simply Folded Zone and the Imbricate Zone (Stocklin 1968;Falcon 1974;Berberian 1995;Sepehr and Cosgrove 2004). Recent studies (Talbot and Alavi 1996;Bahroudi and Talbot 2003;Bahroudi and Koyi 2004;Sherkati and Letouzey 2004;Farzipour-Saein et al 2009a) show that the geometry of the Zagros deformation front and evolving foreland basin has been controlled by at least two different structural parameters: (1) reactivation of basement faults (Hessami et al 2001a;Bahroudi and Talbot 2003;Sepehr and Cosgrove 2005;Ahmadhadi et al 2007;Mouthereau et al 2007a, b;Farzipour-Saein et al 2009a;Nilfouroushan et al 2013;Burberry 2015) and (2) mechanical nature of the sedimentary layers in the ZFTB (Bahroudi and Koyi 2003;Sherkati and Letouzey 2004;Farzipour-Saein et al 2009b). Different evidences indicate that many of the transverse basement faults involve right-lateral strike-slip displacements with dip-slip components (Baker et al 1993;Berberian 1995;Hessami et al 2001b;Bahroudi and Talbot 2003;Sepehr and Cosgrove 2005;Ahmadhadi et al 2007;Farzipour-Saein et al 2009a;Allen 2010).…”
Section: Regional Geologymentioning
confidence: 96%